We are too many : a memoir [kind of] - Pittard, Hannah (Henry Holt and Company, 2023)
"In this wryly humorous and innovative look at a marriage gone wrong, Hannah Pittard recalls a decade's worth of unforgettable conversations, beginning with the one in which she discovers her husband has been having sex with her charismatic best friend, Trish. These time-jumping exchanges are fast-paced, intimate, and often jaw-dropping in their willingness to reveal the vulnerabilities inherent in any friendship or marriage. Blending fact and fiction, sometimes re-creating exchanges with extreme accuracy and sometimes diving headlong into pure speculation, Pittard takes stock not only of her own past and future but also of the larger, more universal experiences they connect with--from the depths of female rage to the heartbreaking ways we inevitably outgrow certain people. Clever and bold and radically honest to an unthinkable degree, We Are Too Many examines the ugly, unfiltered parts of the female experience, as well as the many (happier) possibilities in starting any life over after a major personal catastrophe."--Publisher marketing.